Connectome-based disentangling of epilepsy networks from insular stereoelectroencephalographic leads - Kathrin Machetanz; Eliane Weinbrenner; Thomas Volkmar Wuttke; Silke Ethofer; Randolph Helfrich; Josua Kegele; Stephan Lauxmann; Michael Alber; Sabine Rona; Marcos Tatagiba; Holger Lerche; Jürgen Honegger; et al. (Frontiers in Neurology)
ObjectiveEpilepsy is considered as a network disorder of interacting brain regions. The propagation of local epileptic activity from the seizure onset zone (SOZ) along neuronal networks determines the semiology of seizures. However, in highly interconnected brain regions such as the insula, the association between the SOZ and semiology is blurred necessitating invasive stereoelectroencephalography (SEEG). Normative connectomes on MRI data enable to link different symptoms and lesion locations to a common functional network. The present study applied connectomics to disentangle epilepsy networks from insular SEEG recordings and to describe their relationship to seizure semiology.MethodsWe retrospectively extracted functional networks by normative connectome analysis from 118 insular contacts depicting epileptic discharges during SEEG in 20 epilepsy patients. The resulting epilepsy networks were correlated to the corresponding semiology by voxel-wise regression and multivariate analyses of variances.ResultsEpileptic foci were found in the posterior insula for somatosensory, other sensory and motor seizures, while cognitive and autonomic symptoms were related to the anterior insula. We identified insular connections to the superior temporal gyrus and heschl gyrus in sensory seizures and projections to the somatosensory cortex in somatosensory seizures. Insula-basal ganglia pathways were found in cognitive seizure manifestations, while insular connectivity to fronto-basal regions were strongest in patients with autonomic seizures.ConclusionThe semiology of seizures is mirrored in the functional connectivity of insular epileptic discharges. Combining SEEG and connectomics could provide additional information about seizure propagation within the epilepsy network and might enable new treatment options in the future like deep brain stimulation.